Options for Data Reporting – EITI standard, 2016 : The Good, the Better and the Best - World Bank (World Bank, Washington, DC, 2016)
The Extractive Industries Transparency Initiative (EITI) is an international standard to promote open and accountable management of natural resources. By encouraging governments, extractive companies, civil society and the public to engage in discourse around transparency of the extractive sector, it aims to facilitate the management of a country’s natural resource wealth to benefit all its citizens. The EITI is implemented at the national level. As of June 2016, 51 countries are implementing the EITI in accordance with the 2016 EITI Standard. Since its inception, EITI implementing countries have published EITI Reports covering more than 300 fiscal years. This report provides format options and recommendations for data output for EITI Requirements listed under the 2016 EITI Standard. These recommendations are based on identifying commonly used and evolving data categories under each Requirement and spell out qualitative and quantitative data formats. Where international standards are available and where these are emerging, the report uses these as its basis of recommendations. The recommendations for data outputs are meant to compliment the narrative provided within the Country Report, and is not to be considered a replacement for other reporting requirements under the EITI. The objective of this report is to present, in a structured form, data categories and their reporting formats, that can be used to standardize information generated under each EITI Requirement. The review conducted for this study included a sample of recent EITI Country Reports, as well as other initiatives and industry standards. These recommendations should be considered as a contribution in the efforts towards standardizing data reporting under EITI Requirements, and need to be tested to identify issues with data collection under the headings as categorized in this report.